Geojournalism: An Emerging Discipline and its Application at University of The Bahamas - Stephens, Mark; Yildirim, Tarik Emre (International Journal of Bahamian Studies, 2023)
Geojournalism is a growing field within environmental journalism at the intersection of both eco- and data-journalism. It is a new way to combine maps and data with traditional reporting in online platforms to provide scientific evidence for stories and narrative context for data. However, given its novelty, there appears to be little formal recognition of geojournalism in educational and academic contexts. In this paper, we review tools, techniques, and platforms that can be applied by educators and learners to investigate and report on geographic and environmental issues. We also describe examples of geojournalism (blog, radio show, infographic, photostory, and virtual field trip) resulting from collaboration between Geography and Journalism faculty and students at University of The Bahamas. We propose that geojournalism include geography researchers, educators, students, and citizen scientists sharing their knowledge and data with journalists and as well as being trained in journalism themselves. This study furthers the recognition and formalization of geojournalism in environmental communication and higher education.